Elevated CO2 modulates the effect of heat stress responses in Triticum aestivum by differential expression of an isoflavone reductase-like gene. (29th May 2021) - Shokat, Sajid; Novák, Ondřej; Široká, Jitka; Singh, Sukhwinder; Gill, Kulvinder Singh; Roitsch, Thomas; Großkinsky, Dominik K; Liu, Fulai
Abstract : Distinct regulation of an isoflavone reductase -like gene is associated with differential physiological changes and agronomic performance of wheat genotypes in response to heat and elevated CO2 . Abstract: Two wheat genotypes forming high and low biomass, exhibiting differential expression of an isoflavone reductase -like ( IRL ) gene, and resulting in contrasting grain yield under heat stress field conditions were analyzed in detail for their responses under controlled heat and elevated CO2 conditions. Significant differences in IRL expression between the two lines were hypothesized to be the basis of their differential performance under the tested conditions and their stress tolerance potential. By a holistic approach integrating advanced cell physiological phenotyping of the antioxidative and phytohormone system in spikes and leaves with measurements of ecophysiological and agronomic traits, the genetic differences of the genotypes in IRL expression were assessed. In response to heat and elevated CO2, the two genotypes showed opposite regulation of IRL expression, which was associated with cytokinin concentration, total flavonoid contents, activity of superoxide dismutase, antioxidant capacity and photosynthetic rate in leaves, and cytokinin concentration and ascorbate peroxidase activity in spikes. Our study showed that IRL expression is associated with wheat yield performance under heat stress at anthesis, mediated by diverse physiological mechanisms. Hence, based on our results, the IRL gene is a promising candidate for developing genetic markers for breeding heat-tolerant wheat.